Five new species of Tinodes (Trichoptera: Psychomyiidae) from China - Peng, Lang; Ge, Xin-Yu; Sun, Chang-Hai; Wang, Bei-Xin (Zootaxa, 2022)
Five new species of genus Tinodes Curtis 1834 from China are described, illustrated, and diagnosed based on distinctive characters of male genitalia, including Tinodes falcata n. sp., T. xuzhouorum n. sp., T. shunhuangshanensis n. sp., T. yangae n. sp., and T. lini n. sp. Tinodes falcata n. sp. differs from other members of Tinodes in having an unpaired falcate and strongly sclerotized phallic sheath process. Tinodes xuzhouorum n. sp. differs from T. charmi Malicky 2009 by the relative lengths of the superior appendages and the phallus, the position of the ejaculatory duct, and the angle formed by tergum IX and the superior appendages in lateral view. Tinodes shunhuangshanensis n. sp. can be distinguished from T. sartael Malicky 2017 by the phallic sheath process splitting into paired dorsal branches and an apically incised ventral branch. Tinodes yangae n. sp. differs from T. eris Malicky & Sangpradub 2001 by the dorsal phallic sheath process having extra paired vertical branches. Tinodes lini n. sp. differs from T. dactringa Johanson & Oláh 2008 by the phallic guide with a pair of closely attached dorsal branches.